The Catalyzing Mind Beyond Models of Causality - Cabell, Kenneth R.; Valsiner, Jaan.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
How do we understand and explain phenomena in psychology? What does the concept of (3z(Bcausality(3y (Bmean when we discuss higher psychological functions and behavior? Is it possible to generate (3z(Blaws(3y (Bin a psychological and behavioral science$1 (Blaws that go beyond statistical regularities, frequencies, and probabilities? An international group of authors compare and contrast the use of a causal model in psychology with a newer model$1 (Bthe catalytic model. The Catalyzing Mind: Beyond Models of Causality proposes an approach to the qualitative nature of psychological phenomena that focuses on the psychological significance and meaning of conditions, contexts, and situations as well as their sign-mediating processes. Contributors develop, apply, and criticize the notion of a catalyzing mind in hopes of achieving conceptual clarity and rigor. Disciplines such as philosophy, psychology, semiotics and biosemiotics are used for an interdisciplinary approach to the book. Research topics such as history and national identity, immigration, and transitions to adulthood are all brought into a dialogue with the concept of the catalyzing mind. With a variety of disciplines, theoretical concepts, and research topics this book is a collective effort at an approach to move beyond models of causality for explaining and understanding psychological phenomena.s
Annals of Theoretical Psychology: A Reintroduction. Craig Gruber, Jaan Valsiner, Matthew Clark and Sven Hroar Klempe -- Systematic Systemics: Causality, Catalysis, and Developmental Cybernetics. Kenneth R. Cabell and Jaan Valsiner -- Breaking The Arrows of Causality: The Idea of Catalysis in its Making. Jaan Valsiner -- Cause and Catalyst: A Differentiation. Alaric Kohler -- Catalysis, Cause, and Explanation: An Interdisciplinary Inquiry. Sven Hroar Klempe -- Semiotic Scaffolding: A Biosemiotic Link Between Sema and Soma. Jesper Hoffmeyer -- Catalysis and Scaffolding in Semiotic. Kalevi Kull -- A Systemic Approach to Cultural Diffusion and Reconstruction. Brady Wagoner -- Catalysis and Morphogenesis: The Contextual Semiotic Configuration of Form, Function, and Fields of Experience. Raffaele De Luc Picione and Maria Francesco Freda -- Exploring the Role of Catalyzing Agents in the Transition to Adulthood: A Longitudinal Case Study with Brazilian Youth. Elsa de Mattos and Antonio Marcos Chaves -- Catalysts and Regulators of Psychological Change in the Context of Immigration Ruptures. Irini Kadianaki and Tania Zittoun -- Fostering National Identity, Hindering Historical Understanding. Cesar Lopez, Mario Carretero and Maria Rodrigues-Moneo -- Beyond the Self and the Environment: The Psychological Horizon. Luca Tateo -- Man$1 (Bs Search for Extra-Ordinary Answers in Life: Silence as a Catalyst for Crisis-Solving. Olga V. Lehmann Oliveros -- Semiotic Catalytic Activators: an Early Semioitc Mediation in the Construction of Personal Syntheses. Marcio S. da Silva -- A Structural Systemic Theory of Causality and Catalysis. Aaro Toomela.s
Keywords: Philosophy (General).; Consciousness; Psychology; Personality and Social Psychology; Cognitive Psychology